An Empirical Estimation of The Cost of Capital for Energy Companies. - Yang, Hansen. (Tufts Archival Research Center, 2016)
In this paper, we use purely regression-based analyses to estimate the weighted average cost of capital of energy companies. Our analyses can serve as an alternative approach to the traditional WACC estimation method and a benchmark for practitioners to check their results.